Impacts of Kelvin-Helmholtz billow formation on GNSS radio occultation measurements of sporadic-E - Knisely, Andrew J.; Emmons, Daniel J. (Frontiers in Astronomy and Space Sciences, 2023)
Global Navigation Satellite System (GNSS) Radio Occultation (RO) has shown great promise for monitoring sporadic-E layers. However, extracting sporadic-E information from RO signals remains a difficult task due to the many unknown parameters such as length, intensity, vertical thickness, and small-scale structure or turbulence. To further our understanding of sporadic-E turbulence, we investigate the power spectra of sporadic-E layers during Kelvin-Helmholtz billow formation. Additionally, RO signals traversing the billows are simulated to analyze the impact on both amplitude and phase. From this, we find that the horizontal power spectrum is generally steeper in sporadic-E layers without billow formation, and the spectrum flattens as smallscale structures develop. Additionally, the typical 'U'-shaped RO amplitude profiles produced by sporadic-E layers become asymmetric and less defined as the billows form & progress, showing that a single sporadic-E layer can produce a variety of RO signatures as it evolves over time.Ultimately, these results provide valuable insight for both modeling RO signals through sporadic-E layers and inverting RO data to extract information about the layers.